Separation algorithm of paired carrier multiple access based on independent component analysis - WAN Jian; XU Hua; ZHU Zhong-liang (Tongxin xuebao)
Based on the introduction of paired carrier multiple access（PCMA）technology,a new algorithm was proposed to separate the satellite PCMA downlink mixed signals with independent component analysis（ICA）.The new algorithm utilized maximum negentropy as the separating criterion which could overcome the limitation that the power of two up-link signals could not be different too much.The computer simulations testified the validity of the algorithm.